2002
DOI: 10.1161/01.atv.0000022694.16328.cc
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Reduces Expression of Cytokines Interleukin-6, Interleukin-8, and Monocyte Chemoattractant Protein-1 in Circulating Monocytes From Hypercholesterolemic Patients

Abstract: Objective-A number of studies have shown that statins decrease morbidity and mortality in patients with cardiovascular diseases. The anti-inflammatory effects of statins have recently been implicated in the clinical benefit that can be obtained in the treatment of atherosclerosis. Little is known about the mechanisms by which statins counteract inflammation. Methods and Results-In this study, we asked whether simvastatin can influence in vitro and in vivo production of the proinflammatory cytokines interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
221
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(235 citation statements)
references
References 30 publications
12
221
1
1
Order By: Relevance
“…26 Several investigators demonstrated that high-dose statins inhibit MCP-1 expression by both ECs and macrophages. 27 By inhibiting L-mevalonate synthesis, statins prevent the synthesis of important downstream isoprenoid intermediates of the cholesterol biosynthetic pathway and block the modification of various regulatory proteins. 16,28 Because the inhibition of RANTES and MCP-1 production in vitro was reversed by administration of L-mevalonate, the statin effect may be due to a biosynthetic pathway that involves a mevalonate intermediate or could involve a mevalonatesensitive modification of proteins such as Ras, Rho, PI 3 kinase, or nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several investigators demonstrated that high-dose statins inhibit MCP-1 expression by both ECs and macrophages. 27 By inhibiting L-mevalonate synthesis, statins prevent the synthesis of important downstream isoprenoid intermediates of the cholesterol biosynthetic pathway and block the modification of various regulatory proteins. 16,28 Because the inhibition of RANTES and MCP-1 production in vitro was reversed by administration of L-mevalonate, the statin effect may be due to a biosynthetic pathway that involves a mevalonate intermediate or could involve a mevalonatesensitive modification of proteins such as Ras, Rho, PI 3 kinase, or nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Fluvastatin, atorvastatin, cerivastatin, and simvastatin significantly decrease circulating MCP-1 levels in patients with hypercholesterolemia (58-61). Statins also decrease levels of the chemokine IL-8 (59,62), another important regulator of leukocyte adhesion and chemoattraction. Statin effects on these and other soluble mediators may therefore indirectly alter the conditions for leukocytes to migrate to sites of inflammation.…”
Section: Statins As Antiinflammatory Drugs: Effects On Cells and Tissuesmentioning
confidence: 99%
“…In separate, randomized prospective studies of patients with hypercholesterolemia and hypertension, treatment with simvastatin resulted in decreased circulating IL-1␤, and IL-1␤ production by isolated PBMCs, respectively (82,83). Both atorvastatin and simvastatin significantly decrease levels of circulating IL-6 and TNF␣, in addition to IL-1␤, in patients with hypercholesterolemia (39,41,59,84). Carotid plaques resected from patients taking statins contain significantly lower concentrations of IL-6 (P ϭ 396 ABELES AND PILLINGER 0.0005), suggesting that statins do, indeed, alter local inflammation in atherosclerotic lesions (85).…”
Section: Statins As Antiinflammatory Drugs: Effects On Cells and Tissuesmentioning
confidence: 99%
“…Endothelial dysfunction is also characterized by elevated levels of the vasoconstrictive substance endothelin-1, 13 and statins have also been shown to inhibit the expression of endothelin-1 in vascular endothelial cells. 14 In addition, statins have demonstrated the ability to inhibit platelet aggregation 15,16 and monocyte adhesion to the endothelial surface 17,18 and to possess antioxidant 19 and antiinflammatory activity, particularly the reduction in C-reactive protein levels. 20,21 Although some of these nonlipid effects may be operative even before substantial lipid benefits accrue, others may not be truly independent of lipid reduction.…”
Section: See P 2280mentioning
confidence: 99%